KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING:PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS (STUDI PADA PELANGGAN MOLAK MALIK CAFE KOTA PASURUAN) - AYU ASTRIANA, DIAH (Jurnal Ilmu Manajemen (JIM), 2019)
The purpose of this study is to analyze and discuss the influence of experience marketing on customer loyalty Molak Malik Kafe with satisfaction as an intervening variable. The sampling technique used is non probability sampling with judgmental sampling method. The sample used is 220 people. The population in this study were respondents who had bought food and drinks at least 2x and used spot photos in the last 6 months in Molak Malik Cafe, Pasuruan City, aged 16-35 years. Data analysis using analysis path with AMOS program. The results of the study show that Experiential Marketing has a positive effect on customer loyalty and satisfaction as intervening. In the mediation test Experiential Marketing proved to be partially mediated by satisfaction.Keywords: experiential marketing; loyalty; satisfaction.